Agricultura familiar no Pantanal : sustentabilidade e desenvolvimento do Assentamento Agroana Girau, em Poconé - MT - Correia, Jonas Benevides (2016)
This thesis is themed Family Agriculture in the Pantanal: sustainability and development of Agroana Girau settlement in Poconé - MT, and discusses the social, economic and environmental relations on family agriculture and food production so this community. It describes the project prepared by the Faculty of Economics of UFMT, which aimed to deploy agroecological techniques and make the transition from the mode of production in the settlement. After conducting a diagnosis of the main local needs, was elaborated as a research problem the following question: which social, economic and environmental constraints of the current family farming development model? For the preparation of research papers, defined as main objective to study the implementation of agro-ecological production methods as an alternative to the development model of family farming in Agroana Girau settlement. The specific objectives are: to analyze the initial diagnosis of the interrelationship between the productive activity and the local environment; describe conventional production and marketing of olericulturas as insert location in the regional market; and study the process of introduction of agro-ecological production mode in the settlement. As a theoretical basis the project was based on the concepts of endogenous local development, which together with the principles of agroecology confer the character of economic, social and environmental described by Sachs (2004). Collected up information in interviews and testimonies of farmers and family photos, recording videos, soil samples, water, food, vegetation, for analysis in laboratories. It also used information from the academic activity reports. The methodology and its planning configure an exploratory research and a case study, as described by Yin (2001). After discussions about the two modes of production and marketing processes is an analysis of these results. It presents a proposal for action based on the project carried out, as a complement public policies for family farming. At the end of the dissertation it is concluded that the local market for organic food has conditions for growth since the state imports more than 50% of fresh produce. However, being only the second year of activity, agroecological production in Agroana Girau settlement will face many challenges for its consolidation in Cuiaba and region.